2015
DOI: 10.4038/tar.v26i3.8114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breeding strategies to increase productivity of indigenous chicken in-situ in Bangladesh

Abstract: ABSTRACT. Performance of three generation (G 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…In line with the findings of this study, Haunshi et al (2019) observed the survivability of White Leghorn, Nicobari and Ghagus breeds of chicken as 91.6, 87.1 and 82.9 percent, respectively. However, in contrast to the findings of present study, Islam et al (2015) reported very low survivability (46.55-51.15%) of indigenous chicken In-situ reared under different breeding strategies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In line with the findings of this study, Haunshi et al (2019) observed the survivability of White Leghorn, Nicobari and Ghagus breeds of chicken as 91.6, 87.1 and 82.9 percent, respectively. However, in contrast to the findings of present study, Islam et al (2015) reported very low survivability (46.55-51.15%) of indigenous chicken In-situ reared under different breeding strategies.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, El-Dlebshany (2008) (Islam et al 2015) however it was comparable to the hatchability of eggs in later generations of selection. Hatchability of eggs on fertile egg basis, in all four generations in this study were recorded higher than that of Azharul et al (2005) who obtained 87% for the indigenous chicken in Bangladesh on the same basis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Crossbreeding and upgrading of indigenous chicken was considered the simplest and quickest way to improve indigenous stock for economically significant traits (Padhi, 2016;Mengesha et al, 2022). By introducing upgraded or crossbred genotypes, the egg production at smallholder level might be increased within the existing production system in Bangladesh (Khan et al, 2006;Islam et al, 2015). After 1990, Sonali (RIR♂ × Fayoumi♀) was introduced through Department of Livestock Services (DLS) to increase village level egg and meat production (Ali et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Simple selection selects animals with certain characteristics, and high genetic merit is passed down to subsequent generations. Improvements in the productivity and reproduction of many indigenous breeds have been recorded across numerous generations (Anjum et al, 2012;Islam et al, 2015). With this view, this research is to be conducted to know the genetic potential of indigenous breed Naked neck to know the selective breeding effect in different generations and evaluate production and reproduction performances.…”
Section: Introductionmentioning
confidence: 99%